2005
DOI: 10.1186/1477-3155-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct microcontact printing of oligonucleotides for biochip applications

Abstract: BackgroundA critical step in the fabrication of biochips is the controlled placement of probes molecules on solid surfaces. This is currently performed by sequential deposition of probes on a target surface with split or solid pins. In this article, we present a cost-effective procedure namely microcontact printing using stamps, for a parallel deposition of probes applicable for manufacturing biochips.ResultsContrary to a previous work, we showed that the stamps tailored with an elastomeric poly(dimethylsiloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 14 publications
1
60
0
1
Order By: Relevance
“…Also, the nanoparticles may cause the solvent to be pinned at multiple points within the print area, not just at the perimeter. For comparison, DNA arrays made by direct microcontact printing, a ‘dry’ method that does not involve droplet evaporation, yield uniform spots (35). Additionally, ring formation is not observed with oligonucleotide arrays fabricated by in situ synthesis (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the nanoparticles may cause the solvent to be pinned at multiple points within the print area, not just at the perimeter. For comparison, DNA arrays made by direct microcontact printing, a ‘dry’ method that does not involve droplet evaporation, yield uniform spots (35). Additionally, ring formation is not observed with oligonucleotide arrays fabricated by in situ synthesis (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Whatever the technique, the size of the spots produced by these types of commercial devices ranges between 50 and 500 μm in diameter, depending on the type and the surface chemistry of the substrate (nylon membranes, glass slides, silicon, etc.). An alternative method for the parallel deposition of molecules on functionalized surface is the microcontact printing (μCP), which uses polydimethylsiloxane (PDMS) stamps exhibiting micrometer to nanometer size engraved patterns over large areas (Renault et al 2003;Thibault et al 2005). For higher size reduction, dip-pen lithography or nanodispensing techniques (NADIS) are today the most suitable techniques to reach nanometer scale dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…All of these processes require the chemical functionalization of the reticulated PDMS stamp surface and are not straightforward. Thibault et al [27] showed that, contrary to expectation, unmodified reticulated PDMS stamp surface can retain nucleic acids which can then be transferred onto the substrate surface, enabling a facile route for the production of DNA microarrays. To account for this patterning process using unmodified reticulated PDMS surfaces, these authors showed that DNA transferred onto the target surface originated from nucleic acids retained by low molecular weight (LMW) siloxane fragments present within and at the surface of the cured PDMS stamp [28].…”
Section: Introductionmentioning
confidence: 99%